(untitled) - Mosteller, Frederick (Massachusetts, 1970)
The theory of probability - the mathematics of uncertainty. Some applications of probability to statistical theory. An understanding of the equivalent of high school Algebra II is required for effective learning from this text.
Keywords: Mathematical statistics,Toán thống kê